RANCANG BANGUN SISTEM INFORMASI PENGOLAHAN DATA RUMAH BERSALIN AL-IHRAM DENGAN MENGGUNAKAN METODE WATERFALL - Novita Indri Yani (LPPM Universitas Bina Sarana Informatika, 2011)
With the establishment of data processing information systems at the maternity hospital patients Ikhram, then the existing system is expected to be better than a run for this system. For its development the author did some research method is to observe them in the administration including registration or processing of existing patient data, interviews with the parts involved, and the literature that support the processing of patient data. Tools system that I use include the waterfall, Data Flow Diagram (DFD) normalization. The system was developed with a structured paradigm and the implementation of the programming language the author uses Visual Basic 6.0, which resulted in the processing of patient data, resulting in the patient card, outpatient cards, receipts and statements - statements that are needed. Keywords: Information Systems, Data Flow Diagram, normalization, waterfall